Les médiévistes et l’histoire des femmes et du genre : douze ans de recherche - Didier Lett; Camille Noûs (Genre & Histoire, 2021)
This long historiographical review aims to provide an overview of research on the history of women and gender in Western medieval history since 2008. It highlights the main historiographical evolutions of the last decade by attempting to make an inventory of scientific production mainly in French, English and Italian. In turn, are mentioned, commented on and even criticised, studies on religion (life in monasteries, cultures of nuns, beguines and mystics, holiness, piety of secular women), masculinities, family (paternity, adelphic links...), couples in and out of marriage), sexualities (homosexuality, sexual violence, prostitution), justice, identities, emotions, economy and work, feminine power (queenship) and feminine cultures (literacy and aurality). The proliferation of gender studies over the last twelve years in medieval history proves that the concept has a strong heuristic value and efficiency. This is welcomed for the future of medieval studies.